(untitled) - Weber, Max (Berkeley, Calif., 1978)
Max Weber's Economy and Society is the greatest sociological treatise written in this century. Published posthumously in Germany in the early 1920's, it has become a constitutive part of the modern sociological imagination. Economy and Society was the first strictly empirical comparison of social structures and normative orders in world-historical depth, containing the famous chapters on social action, religion, law, bureaucracy, charisma, the city, and the political community with its dimensions of class, status and power.
Keywords: Sociology,Xã hội học